Dynastic aura: Proximity to the powerful and its promise in corporate South Korea. (September 2021) - Prentice, Michael M.
This article discusses the experiences of high-level managers at a South Korean conglomerate named 'Sangdo' who worked within the corporate group's head office under the owner-executive family. These highly credentialled professionals were attracted to the idea of working directly under or alongside an elite, wealthy corporate dynasty who both owned the conglomerate and were its top executives. Rather than seeing this as a site of inherent conflict between the familial and the professional, I describe how the idea of working alongside and for such elites was enhanced by a 'dynastic aura'. Through the concept of dynastic aura, I highlight how, in South Korea, families that own business groups are objects of public fascination, particularly as indicators of the future of the economy. In the context of Sangdo, I describe how managers were drawn to the potential of working with a new generation of Sangdo ownership, who sought to centralize and systematize expertise within a holding company. I show how this aura figuratively wore off for managers as they came to understand that ownership was just as entangled in the corporate form – not necessarily above or outside of it – as they were. The article highlights how certain aspects of kinship (such as dynasties and generational succession) still animate capitalist labour, even for non-family members. Additionally, the article calls attention to the way that actors engage with and understand powerful actors in their own right, going beyond accounts of anthropologists' own direct encounters with the powerful.